Peningkatan Hasil Belajar Matematika Pokok Bahasan Macam-Macam Bangun Datar Melalui Strategi True or False Pada Siswa Kelas I Semester Genap SDN 005 Bengkong Tahun Pelajaran 2018/2019 - Nuraqsha Restuti (Journal on Education, 2022)
The objectives of this research to improve learning outcomes in grade I students of Mathematics, Basic Subjects of Various Shapes Through True or False Strategies for Class I Students in Even Semesters at SDN 005 Bengkong, Batam City, 2018/2019 Academic Year. The subject of this classroom action research is Mathematics, the subject matter of various kinds of flat shapes by applying True or False learning strategies, to the first grade students of SDN 005 Bengkong, Batam City, with a total of 24 students. The research site for learning improvement is at SDN 005 Bengkong, Batam City. The time of this research was carried out through two cycles, cycle I on January 6 – January 11 2019, cycle II on January 20, 2020 – January 25, 2019. The results of this study were that learning with the True or False strategy had a positive impact on improving mathematics learning outcomes about various types of mathematics. - Kinds of Waking Up Flat in Grade I Students of SDN 005 Bengkong Batam City. This can be seen in Cycle I, from 24 students who completed as many as 14 students (58.3%) and 10 students who had not completed (41.67%). While in Cycle II, there were 20 students (83.33%) who finished and 4 students (16.67%). So, after Cycle II was held, student learning outcomes increased by 25.03%.